(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Pattern generalization is an important aspect of mathematics contained in every topic in teaching. This study aims to investigate middle school students’ generalization of number patterns based on learning style. Descriptive qualitative, portraying or describing the events that are the center of attention (problem-solving abilities, student learning styles) qualitatively.This study explored 4 participants (12 to 13 years old) with their constructed number pattern they had generalized during individual task-based interviews. Questions that include indicators of the problem solving process in terms of student learning styles, and interviews. The data analysis used was namely data reduction, data presentation, drawing conclusions. We found that students who are converger, diverger, accommodator, and assimilator understands the problem by knowing what is known and asked and explains the problem with their own sentences. The converger and assimilator students look back without checking the counts involved, the diverger students do not see other alternative solutions and do not check the counts involved, accommodator students consider that the solutions obtained are logical, ask themselves whether the question has been answered, check the counts that are done, reread the question, and use other alternative solutions. The implication of this study indicated that students of the type of converger, diverger, accommodator, and assimilator are able to solve problems through the stages of implementing plans by interpreting problems in mathematical form, implementing strategies during the process and counting takes place. Based on several studies on pattern generalization, there have not been researchers who have revealed the number pattern generalization of high school students based on learning styles.